Oestrogen receptor distribution related to functional thymus anatomy of the European sea bass, Dicentrarchus labrax - Paiola, Matthieu (2019)
In jawed vertebrates, the crosstalk between immune and endocrine system as well as many fundamental mechanisms of T cell development are evolutionary conserved. Oestrogens affect mammalian thymic function and plasticity, but the mechanisms of action and the oestrogen receptors involved remain unclear. To corroborate the oestrogenic regulation of thymic function in teleosts and to identify the implicated oestrogen receptor subtypes, we examined the distribution of nuclear and membrane oestrogen receptors within the thymus of the European Sea bass, Dicentrarchus labrax, in relation to its morpho-functional organisation. Immunohistological analysis specified thymus histology and organisation in teleosts and described, for the first time, Hassall's corpuscle like structures in the medulla of sea bass. All oestrogen receptors were expressed at the transcript and protein level, both in T cells and in stromal cells belonging to specific functional areas. These observations suggest complex regulatory actions of oestrogen on thymic function, notably through the stromal microenvironment, comprising both, genomic and non-genomic pathways that are likely to affect T cell maturation and trafficking processes. Comparison with birds, rodents and humans supports the thymic localization of oestrogen receptors and suggests that oestrogens modulate T cell maturation in all gnathostomes. (C) 2017 Elsevier Ltd. All rights reserved.